Utilização das metodologias imunoenzimática e reação em cadeia da polimerase (PCR) para detecção e caracterização de Campylobacter spp. em carcaças de frango de corte - Luciana Pimenta Reis (2014)
Foodborne diseases are considered a worldwide public health problem, and bacteria of the Campylobacter spp. type are among the micro-organisms that can be transmitted. In order to detect, describe and measure the presence of Campylobacter spp., 86 chicken carcasses (43 cooled and 43 frozen) collected at a federally inspected slaughterhouse were analyzed. Three different methods were used (immunosorbent assay, Polymerase Chain Reaction - PCR and real-time PCR). Of the 86 samples analyzed with the immunosorbent assay only four (4.65%) tested positive for the Campylobacter spp., and these four positive samples were cooled. Using the PCR method, no samples tested positive; however, the primers used in this method were not considered ideal. Nonetheless, when the real-time PCR method was used, 24 (55.81%) cooled samples and 21 (48.84%) frozen samples tested positive for Campylobacter spp. Out of the samples analyzed in real-time PCR, 40 (46.51%) tested positive for Campylobacter jejuni, 15 (17.44%) tested positive for Campylobacter coli, and in 10 (11.63%) samples both Campylobacter jejuni and Campylobacter coli were detected. There was no observable difference in the presence of Campylobacter spp. between cooled and frozen carcasses. We conclude that the real-time PCR method is optimal for the detection of this pathogen in chicken carcasses.